47.1k views
8 votes
SOMEONE HELP FAST PLEASE!!!

Find the sum for the equation (2m + 2y + 5) and (1m + 7y - 10) where m=2 and y=-1
a. Remember! You need to plug in the values for m and y with the numbers provided.

2 Answers

8 votes

Answer:

-8

Explanation:

2(2) + 2(-1) + 5 + 1(2) + 7(-1) - 10

(4 + -2 + 5) + (2 + -7 - 10)

7 + -15

= -8

User Hiren Prajapati
by
4.9k points
13 votes
Alright let’s start with (2m+2y+5). If m=2 and y=-1, then you can plug in (2(2)+2(-1)+5). 2(2) is 4, so 4+2(-1)+5. 2(-1) is -2, so now 4+-2+5. And addition sign and a negative sigh cancel to make 4-2+5.

Answer: 7

Now (1m+7y-10), again we plug in m=2 and y=-1. (1(2)+7(-1)-10). 1(2) is 2. 7(-1) is -7. So now (2+-7-10), and the addition sign and negative sign make it (2-7-10). 2-7 is -5 minus 10.

Answer: -15

Have a good day mate.
User Acernine
by
5.1k points